Paciente Masculino De 68 años De Edad Con Diabetes Mellitus Tipo ll. - Moran Arboleda, Yadira Dayana (2018)
The present case study is based on a 68 year old male patient. He was diagnosed with diabetes mellitus type II, has excessive urination, fatigue, blurred vision and excessive weight loss, in the anthropometric assessment he has a body mass index of 31.8 kg / m2, according to the cutoff points of the Pan American Health Organization , classification of older adult presents Overweight, to the physical examination presents normal vital signs. It is intended to improve the nutritional status of the patient and establish a meal plan of 2,000kal / day, hypograse high in fiber, low in saturated fats, divided into 5 meals a day, with control of sodium, calcium, vitamin C, provides guidelines therapeutic diet, promotion of physical activity, complete, balanced, healthy diet, suitable for the patien. The nutritional treatment lasts 6 months during 2 days per month through the correct monthly nutritional assistance with improvement in the evolution and quality of life of the patien